2018
DOI: 10.1002/pi.5586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing time and molecular weight on melt memory of random ethylene 1‐butene copolymers

Abstract: The effects of annealing time and molecular weight on the strong melt memory effect observed in random ethylene 1‐alkene copolymers are analyzed in a series of model ethylene 1‐butene copolymers with 2.2 mol% branches. Melt memory is associated with molten clusters of ethylene sequences from the initial crystals that remain in close proximity and are unable to diffuse quickly to the randomized melt state, thus increasing the recrystallization rate. Melt memory persists even for greater than 1000 min annealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 52 publications
0
37
1
Order By: Relevance
“…Concerning the time effect on melt memory, different behaviors have been reported in the literature [3,[5][6][7][14][15][16]. In a recent paper published by some of us [4], it is concluded that depending on the temperature range, different trends can be observed: for materials in Domain III, no effect of time has been observed.…”
Section: Effect Of Time Spent At the Self-nucleation Temperaturementioning
confidence: 97%
See 3 more Smart Citations
“…Concerning the time effect on melt memory, different behaviors have been reported in the literature [3,[5][6][7][14][15][16]. In a recent paper published by some of us [4], it is concluded that depending on the temperature range, different trends can be observed: for materials in Domain III, no effect of time has been observed.…”
Section: Effect Of Time Spent At the Self-nucleation Temperaturementioning
confidence: 97%
“…All these works have focused on the erasure of melt Melt memory effects are considered to have a kinetic nature, since the temperature regions of the different Domains depend on the conditions employed to perform the experiment [2][3][4]. Although some aspects, such as the effect of time spent at T s temperature [3,7,[14][15][16], have attracted attention in the literature, other aspects, such as the effect of cooling and heating rates have not been studied. In the following sections, the different parameters that affect the self-nucleation Domains are studied systematically to provide new insights into the control of melt memory effects by taking advantage of its kinetic nature.…”
Section: Effect Of Time Spent At the Self-nucleation Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The fourth paper was contributed by Prof. Rufina Alamo's group with a deep analysis on the strong memory effects of crystallization unique for random copolymers. The memory is long living at low annealing temperatures and exhibits an activation barrier independent of molecular weight.…”
mentioning
confidence: 99%